WebQuest Technologies: Developing Communicative Sphere of Preschool Children with Down Syndrome - Syzko, Anna; Sushchynska, Tetiana; Anastasova, Natalya; Donchenko, Olha; Dubovenko, Anna (Journal of History Culture and Art Research, 2020)
The article reveals the direction of remedial work, using the WebQuest as a means of developing communicative competence of the children with intellectual impairments in general and with Down syndrome in particular. Within the framework of the study of communicative competence of the children with Down syndrome, we have carried out a theoretical analysis of the literature of domestic and foreign scholars. Based on the analysis of literature sources, the structural components of the communicative sphere of senior preschool-age children with Down syndrome were identified and a diagnostic programme was developed. The study identified and described the peculiarities of the communicative sphere of the child with Down syndrome, namely: a low level of expressive speech, an insufficient level of interest in a joint activity, incomprehension of communication norms and incomprehension of cause-and-effect relationship in communicative situations. The aim of the forming experiment was to develop a methodology for enriching communicative competence of the senior preschool-age children with Down syndrome. The paper describes the specifics of the use of WebQuests for the formation of communication skills during a remedial and developmental process. "A Magic Forest" WebQuest technology, which was developed by us, includes tasks aimed at forming components of communicative competence, the lack of which was revealed during the ascertaining experiment, namely: the development of expressive speech, the development of interest in a joint activity, the development of an understanding of communication norms, understanding cause-and-effect relationship in communicative situations. The article presents the results of experimental verification of the effectiveness of the WebQuest technology in the development of communicative competence of the child with Down syndrome. Such a form of work as WebQuest actuates the cognitive activity of a child with intellectual impairments and makes a remedial and developmental process more effective, interesting, diverse, and modern.